Impact of oral hygiene habits on oral health-related quality of life of in-school adolescents in Ibadan, Nigeria - Lawal, Folake Barakat; Fagbule, Omotayo Francis; Akinloye, Seyi John; Lawal, Taiwo Akeem; Oke, Gbemisola Aderemi (Frontiers in Oral Health, 2022)
Background Recent evidence has shown that the prevalence of periodontal diseases is still high among adolescents and, thus, there is an impetus to promote good oral hygiene habits among them through schools. There is a need to provide baseline data on the oral hygiene habits of adolescents and how it impacts their oral health-related quality of life for appropriate intervention to be instituted. Moreover, oral health-related quality of life describes how oral health affects the daily activities of individuals; thus, it provides a holistic means of involving individuals in making decisions about their oral health including uptake of oral hygiene habits. Aim To assess the impact of oral hygiene habits on adolescents' oral health-related quality of life. Methods A cross-sectional study was conducted among 1,800 adolescents aged 14–18 years attending 36 Senior Secondary Schools in the metropolis of Ibadan, Nigeria. Data were collected using a self-administered questionnaire, which assessed students' sociodemographic characteristics, oral hygiene habits, and oral health-related quality of life with COHIP-SF19. Data obtained was analyzed with SPSS version 25 and the p-value was set at <5%. Results The mean age of the adolescents was 15.16 (±1.16) years. Many 1,094 (60.3%) cleaned their teeth twice or more often daily with 126 (7.0%) cleaning after meals and 1,519 (84.4%) changing their tooth cleaning agent at three months intervals or less. About 1,215 (67.5%) spent three minutes or longer in cleaning their teeth. Only a few 238 (13.2%) cleaned interdentally and 137 (7.6%) used dental floss. The OHRQoL scores of the adolescents ranged from 9–76. A total of 1,612 (93.5%) had at least an impact on their OHRQoL. Those who cleaned their teeth more frequently (twice or more) were more likely to have better OHRQoL (OR = 1.6, 95% CI = 1.1–2.4, p = 0.025) and those who did not clean interdentally were more likely to have better OHRQoL (OR = 2.8, 95% CI = 1.2–6.5, p = 0.014) than others. Conclusion The oral hygiene habits of the adolescents were suboptimal and those who cleaned their teeth twice or more often each day had fewer impacts on their OHRQoL, whereas those who engaged in interdental cleaning had higher impacts on their OHRQoL than others.